Aquaporin 8 expression is reduced and regulated by microRNAs in patients with ulcerative colitis - MIN, Min; PENG, Li-hua; SUN, Gang; GUO, Ming-zhou; QIU, Ze-wu; YANG, Yun-sheng (Chinese medical journal, 2013)
Background Ulcerative colitis （UC） is associated with differential expression of genes involved in inflammation and tissue remodeling. MicroRNA （miRNA） plays an important role in the pathogenesis of UC by regulating the gene expression at the post-transcriptional level and control crucial physiological processes. This study aimed to identify aquaporin 8 （AQP8） expression and its relationship with miRNA in UC patients. Methods Human colon samples, in this study, were obtained from 20 patients with UC and 16 healthy subjects undergoing diagnostic colonoscopy at the Chinese People＇s Liberation Army General Hospital between December 2009 and June 2010. We screened different genes from UC tissues and healthy subjects using genome-wide microarray, quantitative reverse transcription-polymerase chain reaction （qRT-PCR） and Western blotting. Regulation of gene expression by miRNAs was assessed by luciferase reporter construct assays and transfection of specific miRNA mimics and inhibitor. Results We identified that 1596 genes were increased and 1301 genes were decreased in UC patients compared to healthy subjects. Among them, we focused on the analysis of AQP8 which was decreased three folds in UC tissues （P 〈0.01）. The expression of AQP8 mRNA and protein were decreased in UC tissue and tumor necrosis factor （TNF）-α treated HT29 cells compared with controls （P 〈0.05）. We searched candidate target miRNAs of AQP8 through bioformatics and the luciferase report assay analysis indicated that miR-424, miR-195, miR-330, miR-612, and miR-16 which has complementary site in the 3-untranslated region （3＇UTR） of AQP8 could decrease the relative luciferase activities by 10%-45%. Conclusion AQP8 and its relationship with miRNAs may be involved in the pathogenesis of UC.